1993
DOI: 10.1016/0014-5793(93)80013-k
|View full text |Cite
|
Sign up to set email alerts
|

SC‐0051, a 2‐benzoyl‐cyclohexane‐1,3‐dione bleaching herbicide, is a potent inhibitor of the enzyme p‐hydroxyphenylpyruvate dioxygenase

Abstract: Growth inhibition of Lemna gibba plantlets by the bleaching herbicide, SC‐0051 (2‐(2‐chloro‐4‐methanesulfonylbenzoyl)‐1,3‐cyclohexanedione)) was alleviated by the addition of homogentisic acid to the growth medium. Homogentisic acid is a key intermediate in the biosynthesis of tyrosine‐derived plant quinones as well as in tyrosine metabolism. The herbicide prevented the incorporation of radioactivity from [14C]tyrosine into lipophilic plant metabolites and, in rat liver extracts, the herbicide inhibited the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
163
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(170 citation statements)
references
References 15 publications
5
163
0
2
Order By: Relevance
“…AOX can oxidize the ubiquinone pool and uses molecular oxygen as a terminal acceptor. Interestingly, quinone involvement in phytoene desaturation is indicated by the fact that phytoene desaturation is impaired when bleaching cyclohexanedione herbicides (which inhibit the enzyme p-hydroxyphenylpyruvate dioxygenase in the quinone biosynthesis pathway) are applied to plants (Schultz et al, 1993) or when the gene for this enzyme is inactivated by mutation (Norris et al, 1995). In addition, molecular oxygen also has been proposed to be essential for carotene desaturation, at least in nonphotosynthetic plastids (Beyer et al, 1989).…”
Section: Functional Role Of Immentioning
confidence: 99%
“…AOX can oxidize the ubiquinone pool and uses molecular oxygen as a terminal acceptor. Interestingly, quinone involvement in phytoene desaturation is indicated by the fact that phytoene desaturation is impaired when bleaching cyclohexanedione herbicides (which inhibit the enzyme p-hydroxyphenylpyruvate dioxygenase in the quinone biosynthesis pathway) are applied to plants (Schultz et al, 1993) or when the gene for this enzyme is inactivated by mutation (Norris et al, 1995). In addition, molecular oxygen also has been proposed to be essential for carotene desaturation, at least in nonphotosynthetic plastids (Beyer et al, 1989).…”
Section: Functional Role Of Immentioning
confidence: 99%
“…The only native purification achieved so far, from Capsicum chromoplasts (Hugueney et al, 1992), employed Tween 80 at a concentration above the critical micellar concentration (CMC) for solubilization. Also indicative for the membraneintegral localization of phytoene desaturase in Narcissus pseudonarcissus chromoplasts is the mechanistic sequence involving a redox chain using first membranebound quinones (Mayer eta/., 1990;Schulz et al, 1993) and then oxygen (Beyer et al, 1989), as intermediate and final electron acceptor, respectively. This mechanism involves a connection to a membrane-bound nicotinamide adenine dinucleotide (NAD)(P)H-dependent respiratory pathway, also employing quinones as redox-active components and influencing their redox state (Nievelstein etaL, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…HPPDase has been purified from several mammalian and bacterial sources (Wada et al, 1975;Lindstedt et al, 1977;Roche et al, 1982;Endo et al, 1992), and in all cases the active enzyme was found to be a homodimer or, less commonly, a homotetramer, with subunits of approximately 40 to 48 kD. As a result of the central role HPPDase serves in aromatic amino acid metabolism in mammals and plastidic quinone synthesis in plants, a class of competitive inhibitors of HPPDases collectively known as triketones has been developed and used for a variety of clinical and agricultural purposes (Lindstedt et al, 1992;Schultz et al, 1993;Secor, 1994). In humans, the triketone 2-(2-nitro-4-trifluromethylbenzoyl)-1,3-cyclohexanedione and related compounds are used as an alternative to liver transplantation in patients with the otherwise fatal hereditary disorder tyrosinemia type I.…”
mentioning
confidence: 99%
“…In plants, triketones such as sulcotrione (2-[4-chloro-2-nitrobenzoyl]-5,5-dimethylcyclohexane-1,3-dione) are effective bleaching herbicides. Their mode of action arises from a direct inhibition of plastoquinone and tocopherol synthesis and an indirect inhibition of carotenoid desatu-ration (Mayonado et al, 1989;Schultz et al, 1993;Secor, 1994). The latter results in accumulation of the carotenoid biosynthetic intermediate phytoene and photooxidation of the plastid.…”
mentioning
confidence: 99%